Parametric study of retaining wall using plaxis - Maqueline Cyndi, Anak Nap (Universiti Malaysia Sarawak, UNIMAS, 2010)
Retaining wall is a type of generic engineering structure that is employed to restrain lateral forces exerted by a vertical-faced or near-vertical-faced mass of earth. The earth behind the wall may be either the natural embankment or the backfill material placed adjacent to the retaining wall. Retaining walls must be design carefully to withstand lateral pressure of the earth, which tends to cause a failure of the structure. A suitable type of retaining wall to be used depends on the site or soil condition, reciprocal action between soil mass and the retaining wall, magnitude, and the distribution of the lateral earth pressure. In this study, the analysis and the parametric study of a sheet pile wall is done by using finite element software, PLAXIS V8. A finite element model has been developed to analyze the behaviour of sheet pile wall with different value of each parameter such as soil cohesion, angle of internal friction, length of the sheet pile wall, depth of excavation and surcharge load. The different value of the parameter may affect the bending moment and the displacement of the sheet pile wall which are presented and discussed in this study.